Comparison of Intrathecal Fentanyl (25 µg) and 0.5% Hyperbaric Bupivacaine (2.5 Mg) for Labor Analgesia in Multigravida: A Randomized Double-Blind Study - K B Nalini; Raghu K C; Sushmitha Biradar; Kavyasree Katam (Faculty of Medicine-Universitas Airlangga, 2026)
Introduction: Spinal labor analgesia is widely recognized for its rapid onset, reliability, and minimal motor blockade. However, the comparative effectiveness of intrathecal fentanyl and low-dose hyperbaric bupivacaine in multigravida parturients continues to warrant evaluation, particularly with respect to their clinical relevance. Objective: To compare the analgesic efficacy, maternal and fetal safety profiles, and clinical implications of intrathecal fentanyl (25 µg) versus hyperbaric bupivacaine 0.5% (2.5 mg) for labor analgesia. Methods: Seventy ASA II multigravida parturients in active labor were randomized into two groups: Group I received intrathecal fentanyl 25 µg (n = 35), and Group II received intrathecal hyperbaric bupivacaine 0.5% 2.5 mg (n = 35). Pain scores were measured at baseline and at 5-minute intervals following injection. Maternal hemodynamic variables, motor blockade, and side effects were recorded. Neonatal outcomes were assessed using Apgar scores at 1 and 5 minutes. Results: The onset of analgesia was statistically faster in Group I than in Group II (3.8 ± 1.18 min vs. 5.11 ± 1.30 min; P < 0.001), though the difference was not clinically meaningful. No motor blockade occurred in either group. Group II exhibited a statistically significant decline in systolic and diastolic blood pressure within the first 15 minutes (P < 0.001), but these changes were clinically unimportant because they did not require intervention. The duration of the second stage of labor was shorter in Group I (P = 0.032), though again without clinical consequence. Pruritus occurred predominantly in the fentanyl group, while neonatal Apgar scores were comparable across both groups. Conclusion: Both intrathecal fentanyl (25 µg) and hyperbaric bupivacaine 0.5% (2.5 mg) provided effective labor analgesia with favorable maternal and fetal safety profiles. Although statistically significant differences were observed between groups, none translated into clinically significant advantages, supporting the use of either agent for labor analgesia in multigravida parturients.